2019
DOI: 10.3855/jidc.11935
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium kumamotonense in the cervical region in an immunocompetent patient, clinical case report in Mexico

Abstract: Non-tuberculous mycobacterial infection has increased significantly in recent years, especially in emerging countries. We present the case of a 25-year-old male patient, immunocompetent, with cervical lymphadenopathy, identifying Mycobacterium kumamotonense, a rare species in extrapulmonary forms and with a high drug resistance index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…Extensive evaluation was performed prior to surgery, at which time AFB smears from tracheal aspirate and BAL specimens were both negative, but growth of NTM was observed in culture. While previous clinical reports of M. kumamotonensis have documented culture incubation times of more than 2 weeks [ 11 , 22 ], the isolates in this case were recovered within 4–6 days of culture incubation in a patient with severe pulmonary infection.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Extensive evaluation was performed prior to surgery, at which time AFB smears from tracheal aspirate and BAL specimens were both negative, but growth of NTM was observed in culture. While previous clinical reports of M. kumamotonensis have documented culture incubation times of more than 2 weeks [ 11 , 22 ], the isolates in this case were recovered within 4–6 days of culture incubation in a patient with severe pulmonary infection.…”
Section: Discussionmentioning
confidence: 60%
“…Misidentification of M. kumamotonensis as TB has been reported in pulmonary and extra-pulmonary infections [ 11 , 14 , 18 , 22 ], which was attributed to similar clinical manifestations and cross-reactivity of commercial molecular probes, factors that have also been associated with misdiagnosis of a wide variety of other NTM as TB [ 4 , 12 ]. Previous studies have also shown identification of M. kumamotonensis in clinical samples from patients with suspected tuberculosis [ 7 , 10 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing number of NTM isolates are being identified in UK clinical practice with many uncertainties around the management of pulmonary diseases caused by these bacteria. 6 NTM are a group of environmental bacteria commonly isolated from soil, water, animals and food products, meaning we all come into daily contact with them in our lives. The identification of NTM species has been enhanced over the past few years with the introduction of molecular biology techniques.…”
Section: Discussionmentioning
confidence: 99%
“…It often presents unilaterally, single or multiple, and is mainly located in axillary, thoracic, and abdominal lymph nodes. It can present with necrosis, fluctuate, produce ulcers, fistulas in 10% of cases, and discharge caseous material to the outside (scrofula) 26,27 .…”
Section: Cervical Tuberculous Lymphadenitismentioning
confidence: 99%

Extrapulmonary tuberculosis: a public health problem

Hernández-Solís,
Quintana-Martínez,
Quintanar-Ramírez
et al. 2024
CIRUE